'Caring for children who have experienced trauma' – an evaluation of a training for foster parents. Issue 1 (31st December 2020) - Konijn, Carolien; Colonnesi, Cristina; Kroneman, Leoniek; Liefferink, Noortje; Lindauer, Ramón J. L.; Stams, Geert-Jan J. M.
ABSTRACT: Background: Foster children, mostly maltreated in their birth families, may be fostered by parents who know little about the impact of traumatic experiences. Objective: The present study investigated whether the training Caring for Children who Have Experienced Trauma for foster parents can break the negative circle of traumatic stress. The hypothesis was that improvement in parents' knowledge on trauma and mind-mindedness would be associated with a reduction of their parenting stress, children's post-traumatic stress symptoms, and behaviour problems. Method: Forty-eight foster parents ( n female = 35) participated in a pre-test (T1), post-test (T2), and follow-up (T3) assessment. Questionnaires on knowledge on trauma, parenting stress, child post-traumatic stress symptoms, the child's behaviour, and the evaluation of the training were administered. Parents' mind-mindedness was assessed using the describe-your-child interview. Results: Foster parents highly appreciated the training, their knowledge on child trauma increased at T2 and this growth persisted at T3. The parents who gained most knowledge experienced a small decrease in parenting stress at T2. Although the general mind-mindedness did not significantly change, foster parents' mind-mindedness with positive valence substantially increased at T2 and T3, while their mind-mindedness with neutral valence decreased. Foster parents' report on child PTSS declined at T3 compared to T2, but not compared to T1. No changes were found in children's behaviour as reported by the foster parents. The proportion of foster children receiving trauma-focused treatment increased at T2 and T3. Conclusion: This study provides evidence that training in trauma-informed parenting can be effective in improving foster parents' knowledge on the impact of traumatic experiences and in increasing a positive mental representation of their foster child as well as in reducing children's post-traumatic symptoms.